MIKLÓS JANCSÓ’S BUDAPEST - Bednarek, Magdalena (Porównania, 2012)
Miklós Jancsó, the foremost representative of the Hungarian cinema, who won international recognition with his modernistic historiosophic parables (like The Round-up, 1965) tended to situate his films on the Hungarian puszta for almost twenty five years, since 1963. In 1987 the director surprised his audience by setting the Season of Monsters (Szörnyek évadja) partially in the contemporary space of the Hungarian capital city, which has remained present in his films ever since. The spectacular interest in the metropolis in the times of the political transformation, reflected the author’s specific, postmodern, postcolonial world view. The topic of the article is the topography of Budapest in the films by Jancsó.